Analisis Etnosains dalam Tradisi Ngawuwuh di Kabupaten Garut untuk Pembelajaran IPA - Warliani, Resti; Sriyati, Siti; Liliawati, Winny (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
This study aims to examine the Community Knowledge of the Ngawuwuh Tradition through an Ethnoscience Approach. Ethnoscience is an approach that involves the reconstruction of indigenous knowledge into scientific knowledge. The research method employed is descriptive qualitative research. Data collection was conducted through observation, interviews, and literature review. The results of the study indicate that the Ngawuwuh Tradition has various benefits and values of goodness. The indigenous knowledge of the community regarding the Ngawuwuh tradition is obtained from experiences passed down through generations. Based on the scientific analysis, the integration of the Ngawuwuh Tradition as a form of local wisdom is found to have relevance to the science curriculum at the junior high school level, thereby making it a meaningful learning resource for students. Keyword: Ethnoscience; Science Education; Spice Beverage